Spray pyrolysis of Low Carbon Steel by Polymer Matrix Composite - Mahmood, Ibtihal A.; Farhan, Malia M.; Mohammed, Noora T. (Nahrain University College of Engineering Journal, 2017)
In this research study the effect of spray pyrolysis that coating low carbon steel with epoxy reduced corrosion rate by (89.4%), while coated low carbon steel with epoxy composite reinforcement at 2%wt of (Al,TiO2, and Zn) was result the corrosion rate of coated specimens with epoxy composites reinforcement (Al, TiO2, and Zn) are lower than coated specimens with epoxy by (73.42%,91.75%,97.9%) respectively. The weight loss of low carbon steel coated with epoxy at90ºand 300 impingement angles are lower than those of uncoated specimens of low carbon steel by (51.06%,43.2%) respectively ,while the weight loss at90ºand 30º of coated specimens with epoxy composites reinforcement (Al,TiO2) lower than coated specimens with epoxy by (34.78%,17.39%)and (47.61%,23.80%) respectively. The weight loss of erosion characteristics at90ºand 300 of coated specimens with epoxy composites reinforced (Zn) are higher than coated specimens with epoxy by (34.78 %, 28.57%) respectively. The wettability determine by measuring the contact angle that are small than70º signifies hydrophilic surfaces have high surface energies and good wettability. The adhesive strength of coated specimens with epoxy composite has low adhesive strength than that in coated specimens with. The used (AFM) to showed surface morphology and surface roughness of coated specimens with epoxy and epoxy composites .The Pore Size measurement of specimens surfaces coating by (SEM), signifies each type of coated specimens with epoxy composites decreased than with epoxy.